Divination As A Moral Compass And Physical Imagery Of God In African Traditional Religion (Architecture Image Studies, 2026)
Divination is a pivotal aspect of African Traditional Religion (ATR). In African indigenous cosmologies and spiritual systems, divination is the means through which the Divine to speak with humans, offering insight, guidance, and solutions to community and individual. This communicative role is what is referred to as prophetic role of divination. Divination also performs diagnostic and therapeutic role, aiming to identify the hidden causes of tragedies, illnesses, and social strife and proposing solutions. Oracles, spirit possession, and symbolic items help diviners communicate with the spiritual world. Divination is examined as a religious activity, epistemic framework, and moral compass in African world view. It emphasizes its responsibilities in justice, leadership, health, and ethics, highlighting its relevance in current African spiritual life and its similarities to prophetic traditions in global religion. This research adapts a qualitative methodology, using ethnographic fieldwork, practitioner and community interviews, and historical text analysis for its data analysis. Kleinhempel's African Indigenous Knowledge Systems (AIKS) and Mezirow's Transformational Theory underpin this work. These theories suggest that divination as a cultural epistemology bridges the spiritual and physical. Findings reveals that divination rituals are rites of passage, helping people through personal crises and self-discovery. Diviners also mediate conflicts and promote community harmony. The study recommends that diviners and modern medicine should collaborate to provide holistic care.